Peningkatan Kualitas Masyarakat dan Lingkungan di Lombok melalui Program Pengabdian Global Volunteering Exchange 2025 yang Difasilitasi OIA UNRAM - Fiki Adrian; Vici Handalusia Husni; Siti Rafhanah Binti Suwandi; Almer Alim Ragas (Yayasan Literasi Sains Indonesia, 2025)
The role of the Office of International Affairs (OIA) at Mataram University in supporting international cooperation is crucial in efforts to support the sustainable development agenda. This outreach activity aims to analyze the contribution of the Global Volunteering Exchange 2025 program, a collaboration between the OIA at Mataram University and UiTM Shah Alam, Malaysia, in supporting the achievement of the Sustainable Development Goals (SDGs). The activities were carried out through four main pillars: (1) mangrove planting and beach cleanup, (2) hygiene education, (3) STEM programs, and (4) cultural exchange. These four pillars are directly linked to relevant SDG targets. The methods used included field observations, interviews with participants, and documentary studies. The results of the activity indicate that the program successfully enhanced the awareness and capacity of the local community in Lombok in terms of environmental, health, education, and cross-cultural understanding. The program also underscores the role of the OIA as a strategic facilitator in bridging international collaboration for sustainable local development. Recommendations from the activity include the need for program continuity and increased community participation to ensure that benefits are distributed equitably.